Non-invasive Imaging Techniques: From Histology to In Vivo Imaging: Chapter of Imaging in Oncology - Bocklitz, Thomas; Silge, Anja; Bae, Hyeonsoo; Rodewald, Marko; Legesse, Fisseha Bekele; Meyer, Tobias; Popp, Jürgen (Springer, 2020)
In this chapter, we will introduce and review molecular-sensitive imaging techniques, which close the gap between ex vivo and in vivo analysis. In detail, we will introduce spontaneous Raman spectral imaging, coherent anti-Stokes Raman scattering (CARS), stimulated Raman scattering (SRS), second-harmonic generation (SHG) and third-harmonic generation (THG), two-photon excited fluorescence (TPEF), and fluorescence lifetime imaging (FLIM). After reviewing these imaging techniques, we shortly introduce chemometric methods and machine learning techniques, which are needed to use these imaging techniques in diagnostic applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Chemometrics; Coherent anti-Stokes Raman scattering (CARS); Fluorescence lifetime imaging (FLIM); Machine learning; Non-invasive imaging; Raman spectral imaging; Second-harmonic generation (SHG); Stimulated Raman scattering (SRS); Third-harmonic generation (THG); Two-photon excited fluorescence (TPEF)